Blue LED light exposure develops intracellular reactive oxygen species, lipid peroxidation, and subsequent cellular injuries in cultured bovine retinal pigment epithelial cells. (October 2013) - Nakanishi-Ueda, T.; Majima, H. J.; Watanabe, K.; Ueda, T.; Indo, H. P.; Suenaga, S.; Hisamitsu, T.; Ozawa, T.; Yasuhara, H.; Koide, R.
Abstract The effects of blue light emitter diode (LED) light exposure on retinal pigment epithelial cells (RPE cells) were examined to detect cellular damage or change and to clarify its mechanisms. The RPE cells were cultured and exposed by blue (470 nm) LED at 4.8 mW/cm2. The cellular viability was determined by XTT assay and cellular injury was determined by the lactate dehydrogenase activity in medium. Intracellular reactive oxygen species (ROS) generation was determined by confocal laser microscope image analysis using dihydrorhodamine 123 and lipid peroxidation was determined by 4-hydroxy-2-nonenal protein-adducts immunofluorescent staining (HNE). At 24 h after 50 J/cm2 exposures, cellular viability was significantly decreased to 74% and cellular injury was significantly increased to 365% of control. Immediately after the light exposure, ROS generation was significantly increased to 154%, 177%, and 395% of control and HNE intensity was increased to 211%, 359%, and 746% of control by 1, 10, and 50 J/cm2, respectively. These results suggest, at least in part, that oxidative stress is an early step leading to cellular damage by blue LED exposure and cellular oxidative damage would be caused by the blue light exposure at even lower dose (1, 10 J/cm2).